2017
DOI: 10.1186/s13053-017-0073-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of psychosocial aspects in participants of cancer genetic counseling

Abstract: BackgroundThe instrument called “Hospital Anxiety and Depression Scale” (HADS) is frequently used to evaluate anxious and depressive symptomatology in patients who receive Cancer Genetic Counseling (CGC). However, this instrument cannot identify all of the psychosocial factors, such as the antecedents of the patients’ emotional states or their concerns. The objective of the present research was to compare cases detected with psychosocial alterations by means of HADS and a Psychological Health Interview (PHI).M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
(31 reference statements)
1
7
0
Order By: Relevance
“…When receiving a positive genetic test result, women’s emotions ranged from extremely negative (e.g., depression/loss, anger, guilt, frustration) to extremely positive (e.g., empowerment and self-advocacy). Prior research has also found similar emotional ranges in this population ( Hesse-Biber, 2018 , Cicero et al, 2017 , Gonzalez-Ramirez et al, 2017 , Oberguggenberger et al, 2016 , Wenzel et al, 2012 ), mostly describing negative emotions, whereas the current study found they coexisted in relation to risk status ( Peshkin et al, 2016 ). Also consistent with previous research, participants described themselves as “pre-vivors”, not fitting into their own cancer-oriented category (patient or survivor) ( Dean, 2016 , Dean et al, 2017 , Dean and Rauscher, 2017 , Getachew-Smith et al, 2019 , Herndl, 2014 ).…”
Section: Discussionsupporting
confidence: 67%
“…When receiving a positive genetic test result, women’s emotions ranged from extremely negative (e.g., depression/loss, anger, guilt, frustration) to extremely positive (e.g., empowerment and self-advocacy). Prior research has also found similar emotional ranges in this population ( Hesse-Biber, 2018 , Cicero et al, 2017 , Gonzalez-Ramirez et al, 2017 , Oberguggenberger et al, 2016 , Wenzel et al, 2012 ), mostly describing negative emotions, whereas the current study found they coexisted in relation to risk status ( Peshkin et al, 2016 ). Also consistent with previous research, participants described themselves as “pre-vivors”, not fitting into their own cancer-oriented category (patient or survivor) ( Dean, 2016 , Dean et al, 2017 , Dean and Rauscher, 2017 , Getachew-Smith et al, 2019 , Herndl, 2014 ).…”
Section: Discussionsupporting
confidence: 67%
“…An European study found that at the pre‐GT moment there was not the presence of anxiety and depression symptoms . On the other side, previous data from the literature showed that the HADS application is not enough to identify psychological alterations, and need the application of other tools to complement the evaluation . This is why it is important to highlight the data from the qualitative analysis that reveal the presence of the “attitudes, feelings and emotions” category, which shows that the participants experience worries and negative feelings that might interfere with aspects of anxiety and depression.…”
Section: Discussionmentioning
confidence: 97%
“…During the GCRA, some patients might develop anxiety and depression; anguish due to fear of the unknown; and psychological problems related to living with cancer, hereditary predisposition and family issues . Some patients commonly seek psychological help during counseling to discuss problems concerning self‐acceptance and family dynamic issues, such as difficulties in family communication, worries about stigma and effects on future family generations …”
Section: Introductionmentioning
confidence: 99%
“…About 25% of patients who attend genetic counseling experience clinically significant levels of anxiety, and anxiety levels have been associated with decision making and adherence to screening methods and to risk-reduction measures (González-Ramírez et al, 2017). Psychoeducation, a form of psychosocial intervention, has been well documented in the literature to improve coping among individuals with mental illness (Bevan Jones et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Prior to genetic testing, mental health history should be considered because individuals with a psychiatric history may be at greater risk for anxiety post-genetic testing (Hirschberg, Chan-Smutko, & Pirl, 2015). Useful screening tools, such as the psychosocial aspects of hereditary cancer questionnaire and the psychological health interview, assess psychosocial functioning of individuals who intend to undergo genetic counseling and testing (González-Ramírez et al, 2017). These tools may facilitate greater completion of genetic testing, particularly among multiethnic women, who are more likely to experience cancer health disparities.…”
Section: Implications For Nursingmentioning
confidence: 99%